Tumor Delivery of Chemotherapy Combined with Inhibitors of Angiogenesis and Vascular Targeting Agents - Cesca, Marta; Bizzaro, Francesca; Zucchetti, Massimo; Giavazzi, Raffaella (Frontiers in Oncology, 2013)
Numerous angiogenesis-vascular targeting agents have been admitted to the ranks of cancer therapeutics; most of them are used in polytherapy regimens. This review will address recent progress together with our preclinical experience in combining angiogenesis inhibitors, mainly acting on VEGF/VEGFR pathways and vascular targeting agents with conventional chemotherapy and discuss the critical factors that determine the outcome of these treatments. Molecular and morphological modifications of the tumor microenvironment associated to drug distribution and activity will be reviewed. Finally modalities to improve drug delivery and strategies for the optimization of combination therapy will be addressed.